Contactless temperature measurements under static and dynamic reaction conditions in a single-pass fixed bed reactor for CO2 methanation. (May 2018) - Schüler, Christian; Wolf, Moritz; Hinrichsen, Olaf
Graphical abstract: Highlights: Contactless temperature measurements in a powder fixed bed, applied in CO2 methanation. Spatial temperature profiles at laboratory scale, under static and dynamic reaction conditions. Impact of different fixed bed designs and dilution with inert material on heat removal. In situ monitoring of deactivation of catalysts. Abstract: Resolving the temperature profile in catalytic fixed bed reactors is essential for the investigation of reactions. However, this is not readily possible at laboratory scale without affecting the flow regime. Thermography tracks temperature profiles contactless with a high spatial resolution and without influencing the flow regime in the reactor. This study applies thermography for a powder fixed bed reactor at laboratory scale. A pa​rameter investigation was conducted to identify the dependency of hot spot temperatures during the highly exothermic CO2 methanation reaction on major process parameters like reactant gas dilution, volume flow and cooling temperature. Further, the impact of an upstream cold bed on the temperature distribution in the catalytic bed was investigated. It was found that the cold bed was able to remove the heat of reaction efficiently to prolong an overheating of the catalyst bed. Thermography was also used to study a dynamic phenomenon, namely the in situ sulfur poisoning of a nickel-alumina catalyst. The temperature of the fixed bed was thereby spatially resolved at any point in time during the reaction. It was found that poisoning causes the reactive zone to move through the catalytic bed at a constant velocity. A simple poisoning model was applied to correlate the observed moving velocity to the catalyst's specific active surface area as determined by static H2 chemisorption at room temperature.